2011
DOI: 10.21608/jfds.2011.81959
|View full text |Cite
|
Sign up to set email alerts
|

Making of Low Fat Ras Cheese Using Fat Replacer

Abstract: Seven Ras cheese treatments were made to study the effect of replacing milk fat with Novagel® RCN15 (a carbohydrate-based fat replacer) on the quality of low fat Ras cheese. Control cheeses were made from cow's milk containing 3.0% fat, another three Ras cheese treatments were made from the same milk but were standardized to 2.0% fat with adding Novagel® at the rate of 0.0, 0.25% and 0.50% respectively. The other three Ras cheese treatments were made from cow's milk standardized to 1.0% fat with adding Novagel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…The increase in WSN and NPN values could be attributed to the breakdown of proteins in the cheese facilitated by milk and rennet enzymes, as well as other microbial activities, as suggested by El-Zeini et al (2007). This is possibly attributed to moisture evaporation, Kebary et al (2006) observed a significant decrease in the moisture content of Domiati cheese as the pickling period progressed, whereas the total solids (TS) values increased significantly. As outlined by Schar and Bosset (2002), the primary determinants affecting cheese alterations during storage are product composition, processing techniques, packaging methods, and storage conditions (including duration and temperature).…”
Section: Resultsmentioning
confidence: 90%
“…The increase in WSN and NPN values could be attributed to the breakdown of proteins in the cheese facilitated by milk and rennet enzymes, as well as other microbial activities, as suggested by El-Zeini et al (2007). This is possibly attributed to moisture evaporation, Kebary et al (2006) observed a significant decrease in the moisture content of Domiati cheese as the pickling period progressed, whereas the total solids (TS) values increased significantly. As outlined by Schar and Bosset (2002), the primary determinants affecting cheese alterations during storage are product composition, processing techniques, packaging methods, and storage conditions (including duration and temperature).…”
Section: Resultsmentioning
confidence: 90%